Tall Buildings and Land Values: Height and Construction Cost Elasticities in Chicago, 1870–2010 - Ahlfeldt, Gabriel M.; McMillen, Daniel P. (The Review of Economics and Statistics, 2018)
Despite unprecedented vertical growth in large cities, the economics of skyscrapers remain understudied. We combine data on tall buildings with a panel of land prices covering 140 years to analyze the determinants of urban heights. We provide estimates of the land price elasticity of height, the height elasticity of construction cost, and the elasticity of substitution between land and capital for tall buildings. The land price elasticity of height increased substantially over time, and it is larger for commercial than for residential buildings, which suggests that the supply side helps to produce the typical segregation of urban land uses.